Effect of chromium-methionine and zinc-methionine supplementation on histological changes of Awassi lamb testicles - Hamad, Aslam Saud Alwan; Hassan, Shaymaa Ali (Edelweiss Applied Science and Technology, 2025)
This study was conducted in the sheep field of the Animal Production Department at the College of Agriculture / Tikrit University for the period 25 October 2021 to 1February 2022 (70 days) with the aim of measuring the effect of adding both Chromium- Methionine (Cr-M) and Zinc Methionine (Zn-M) on histological changes in the testicles of Awassi lambs. 24 lambs aged 4-5 months were distributed equally into four groups (group / 6 lambs), the initial weight was 25.35 ± 2.25 kg, the first group (T1) was not given only the basic feed (control), the second group added 1 gm Cr-M / 100 kg of live weight, the third group was given 0.33 gm of Zn-M / 100 live weight and the fourth group was given 1 gm Cr-M + 0.33 gm Zn-M /100 live weight. Tissue samples were taken from the testicles of lambs up on removal from the body, and the changes and histological components were studied using fixation and staining techniques to study the changes in the seminiferous tubules and interstitial cells including the thickness of the basement membrane. The results showed that treatment with T2 and T3 led to a significant improvement in the histological structures of the testicle, as well as an increase in the diameter of the seminiferous tubules and an increase in the thickness of the basement membrane. It was noted that there was an increase in the activity of sperm formation compared to the control group. Moreover, the T4 group was the most responsive to treatment, as the results showed a significant improvement in all histological parameters, as well as an increase in the density of sperm cells, and a decrease in amyloid deposition and necrosis. From this, we conclude that the addition of Cr-M and Zn-M, especially when added together, improves the health of the testicles and supports the production of sperm cells.